Effect of natamycin, nisin and glycerol on the physicochemical properties, roughness and hydrophobicity of tapioca starch edible films - Ollé Resa, Carolina Patricia (2014)
In this paper, films based on tapioca starch and containing nisin, natamycin and glycerol were characterized in relation to their physicochemical properties, roughness and hydrophobicity. The content of glycerol affected the mechanical properties of the films studied and the roughness and it was observed an increase in WVP with the increase in glycerol content. The addition of antimicrobials affected the mechanical properties, being nisin the one that produced the greater decrease in the Young modulus. The color was highly affected by the joint presence of natamycin and nisin, which increased the yellow index. The contact angle increased with antimicrobial addition indicating a decrease in hydrophilicity. Nisin also affected the roughness of the films. Water vapor permeability was slightly reduced by the presence of natamycin. It was observed that water vapor permeability and contact angle were correlated with the roughness of the films.